STUDY OF SERVICE SPEED AND SERVICE SCAPE AS A BASIC STRATEGY TO INCREASE LOYALTY BY EVALUATING CUSTOMER SATISFACTION AT PT. BANK MANDIRI PERSERO (SOLO BRANCH) - Pramesty Wahyu Istyaningsih; S Fatonah; NI Susanti (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to determine and analyze empirically the effect of service speed and service scape on customer satisfaction and loyalty at PT. Bank Mandiri Persero (Solo Branch). The analysis techniques used are validity and reliability, linearity, regression, path analysis, t-test, F, coefficient of determination, and correlation analysis. Hypothesis Test Results: service speed has a positive and significant effect on customer satisfaction. Service scape has a positive and significant effect on customer satisfaction. The speed of service has a positive and significant effect on customer loyalty. Service scape has a positive and significant effect on Customer Loyalty. Customer satisfaction has a positive and significant effect on Customer Loyalty. The result of F in the second equation is known to be the magnitude of the value of F = 288.445 significance of 0.000<0.05, so it can be concluded that together the free variables have a significant effect on customer loyalty in PT. Bank Mandiri Persero (Solo Branch). The result of the value of R2 can be explained by the variables of service speed, service scape, and customer satisfaction as an intervening variable of 92.6%, and the remaining 7.4% is explained by other variables outside the research model in the form of interest rates, service quality, and so on. The results of the path analysis show that: The indirect effect of service speed on loyalty is an effective path. The service scape's indirect influence on loyalty is an effective pathway.